Non-Pharmacological Behavior Management techniques in Pediatric Dentistry: A Narrative Review - Naeem, Fareen; Naeem, Sajjal (Indus Journal of Bioscience Research, 2025)
A proper communication combined with a caring attitude develops sound rapport with any paediatric patient. Non-pharmacological behaviour management techniques enable paediatric dentists to successfully alleviate behavioural problems by matching their selection of techniques to that of the child’s style of interaction. On the other hand, few aggressive techniques applied in childhood have been implicated as being prominent factors in the behaviour of developed adult patients with dental phobias. Behaviour management strategies involving non-pharmacological intervention during dental procedures should be considered to attain safe and successful treatment outcomes. This study gives the review of use and the completeness of treatment with these interventions. To mitigate these feelings, it is crucial that the dentist knows and applies behaviour management techniques, adapting them individually to each child and establishing a relationship of trust with both the child patient and their parents or guardians-. This approach aims to minimize fear and anxiety, reducing the chances of behavioural problems, resulting in safe and smooth care.